UNGKAPAN DALAM NASKAH BOCCO TALLU: SEMANTIK - Wahyuddin Wahyuddin; Nurhayati Nurhayati; Ikhwan Ikhwan (Universitas Hasanuddin, 2017)
This study used the qualitative descriptive method. The data was collected through observation and interview. The data was analyzed through coding and reducing. The researcher interviewed the cultural observer and drew the conclusion of manuscript contribution aspects. The result is as follows. First, the analysis of manuscript discourse aspects was observed with two methods, linguistic and structural methods. The linguistic aspect consist of, intentionality, and acceptability of Bocco Tallu manuscript. The structural method consist of words, phrases, sentences, stanzas. Second,the analysis of social cultural context of Bocco Tallu manuscript consist of social level (class social), traditional marriage, leadership concepts, arts, and religious system of Mandar tribe. Third, social cultural context of Bocco Tallu manuscript gave contribution to harmonious society in sociallife of Mandar tribe that is signed with ceremony performed once four years in the presence of all public figures and no other nobles. Having done some analyzes on this text shows the phrases that lead to the concept of power and history in Mandar, especially the kingdom of Alu, Tara Manu 'andSendana.Key words: Manuscripst, Bocco tallu, semantic, culture, structural methode